Czy gniew zawsze jest grzechem? - Królikowski, Janusz (Verbum Vitae, 2018)
The question of wrath constitutes an essential problem which for centuries has found its place at the centre of philosophical and theological reflection. Wrath has been described as one of the most destructive of spiritual vices. Assuming this point of view, Christian tradition posed a question long ago as to whether such a unilateral answer is sufficient. Consider that even God is sometimes wrathful, that Christ focused his wrath on the merchants in the temple, and that man and the world will suffer His wrath on the day of judgment. Saint Gregory the Great stated explicitly that wrath, used in a just cause, may be a manifestation of zeal. Saint Thomas Aquinas, in the context of medieval tradition, which devoted a lot of attention to capital vices, demonstrated coherently that wrath can be decent, and in some cases plays an irreplaceable role. Therefore, even a “holy wrath” is possible.